TINGKAT KEPUASAN KONSUMEN TERHADAP RESTORAN HAPPY COW STEAK BOGOR JAWA BARAT - Ayumi Fitriani Gunawan; Wahyu Budi Priatna (Forum Agribisnis, 2015)
Happy Cow Steak is a restaurant in Bogor which offers western menu with steak as its main product. The aim of this research was to find out the characteristic of Happy Cow Steak’s consumers, buying decision process, and consumer satisfaction. There were 90 respondents participating in this reserach. The methods used in this study were descriptive analysis, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The research showed that the majority of consumers who visited Happy Cow Steak Restaurant were women, 21-30 years old, income between Rp 500.000 to Rp 1.499.999 per month, bachelors and senior high school, graduate students, not married, and lived in Bogor. There were five stages which the happy cow steak consumers had in their buying decision making process, i.e. need recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. Importance Performance Analysis (IPA) showed that the steak cutlery availability, restaurant cleanness, and restaurant comfort were the priority to be improved to meet customer satisfaction. Based on Customer Satisfaction Index (CSI) test, consumer satisfaction level of Happy Cow Steak Restaurant was 71, 94 percent implying that the customers were satisfied.